Perkembangan Resistensi Escherichia coli terhadap Oksitetrasiklin - Soedarmanto Indarjulianto; Alfarisa Nururrozi; Yanuartono Yanuartono; Rusmihayati Rusmihayati; Sitarina Widyarini; Puspa Wikan Sari; Vembriarto Jati Pramono (Jurnal Sain Veteriner, 2018)
Antimicrobial resistance is amongst the primary concern in the field of veterinary medicine worldwide. The research was conducted to evaluate the resistance of Escherichia coli due to inappropriate antibiotic treatment. Escherichia coli in this research was cultured in vitro using 5-ml Tryptone Soya Broth (TSB), which was mixed with an antibiotic, then was incubated at 37 0C for four days (stage I). Subsequently, a part of the culture was transferred  into another 5-ml TSB and incubated at 37 0C for four days (stage II). This procedure was undertaken continuously for stage III, IV, V,and VI (until day 24). Antibiotics in this research was oxytetracycline with three various doses, which are lower dose (1 mg/ml), normal dose (2 mg/ml), and higher dose (8 mg/ml). The development of the antrimocobial resistance was evaluated every four days, using disk diffusion method and the data were analysed descriptively. The results showed that the normal and higher doses of oxytetracycline has the same rate (day 16) in causing E. coli resistant to oxytetracycline. Therefore, the treatment of oxytetracycline with a normal and higher doses continuously could accelerate the emergence of antimicrobial resistance in Escherichia coli.